2002
DOI: 10.1645/0022-3395(2002)088[0730:ccolti]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Component Community of Larval Trematodes in the Mudsnail Hydrobia Ventrosa: Temporal Variations in Prevalence in Relation to Host Life History

Abstract: Temporal variations in the prevalence of larval trematodes in the short-lived prosobranch mudsnail Hydrobia ventrosa (Montagu) were investigated in relation to host life history and season for 4 successive years in temperate windflats of the southern Baltic Sea. The component community of trematode larvae in H. ventrosa comprises at least 10 species; families (and species) represented include Notocotylidae (1), Echinostomatidae (1 or 2), Heterophyidae (2), Monorchidae (1), Microphallidae (3 or 4), Psilostomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 32 publications
2
25
0
3
Order By: Relevance
“…Generally, larger (typically assumed to be older) snails are more likely to be infected with parasites than smaller snails due to an increased opportunity to become infected over time (Hughes and Answer 1982, James 1968, Kube et al 2002, Matthews et al 1985, Pohley 1976. We found few small snails (<14 mm) to be infected.…”
Section: Discussionmentioning
confidence: 66%
“…Generally, larger (typically assumed to be older) snails are more likely to be infected with parasites than smaller snails due to an increased opportunity to become infected over time (Hughes and Answer 1982, James 1968, Kube et al 2002, Matthews et al 1985, Pohley 1976. We found few small snails (<14 mm) to be infected.…”
Section: Discussionmentioning
confidence: 66%
“…Other studies have reported different seasonal patterns, with lows in prevalence during winter and spring and peaks in summer (e.g. Hughes & Answer 1982, Kube et al 2002b or similar patterns of maximum levels in winter and spring (e.g. Al-Kandari et al 2000).…”
Section: First Intermediate Snail Hostsmentioning
confidence: 94%
“…Seasonal changes in trematode prevalence in snail hosts have been attributed to the life history of the snail host, e.g. age structure, recruitment or mortality, seasonal changes in ambient temperatures or the biology of the final hosts, including abundance or behaviour (Kube et al 2002b and references therein). Also, seasonal infection patterns in snail hosts have been linked to infection-status-specific winter migration toward low shore and subtidal areas (Sindermann 1960, Sindermann & Farrin 1962, a possibility that remains unexplored in the system studied here but that may account for some of the patterns observed.…”
Section: First Intermediate Snail Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst in short-lived (< 2 years) gastropods the observed dynamics are largely attributable to life history characteristics of the host (Esch and Fernandez 1994, Field and Irwin 1999, Kube et al 2002, temporal patterns in long-lived hosts are often inconsistent and causes of variation in the frequency of infection are less clear (Sindermann and Farrin 1962, Esch and Fernandez 1994, Ngo and Choi 2004. Similar to the findings of previous investigations (Robson and Williams 1970, Lang and Dennis 1976, Sannia and James 1978, Hughes and Answer 1982, which revealed an increase in infection rates during the warmer months of the year, our study showed prevalence of Echinostephilla patellae infections in Patella vulgata to peak in September, suggesting recent miracidial invasions.…”
Section: Discussionmentioning
confidence: 99%